Síntese e aplicação de nanocristais semicondutores inorgânicos ternários - Matos, Charlene Regina Santos (2016)
In this work, semiconductor nanocrystal alloys (NCs), ZnCdTe and MgCdTe were obtained by the bottom-up approach in aqueous synthesis assisted by conventional and microwave-assisted hydrothermal route. Different synthesis variables such as pH, capping agent (mercaptopropionic acid and glutathione), Zn/Cd ratio and time were used for ZnCdTe nanocrystal synthesis. For MgCdTe synthesis, pH was kept constant while time, Mg/Cd ratio and capping agent were evaluated. UV-Vis absorption and emission spectra (PL) showed composition dependence (Zn / Cd and Mg / Cd) which was altered depending on the synthesis parameter. These results were corroborated by transmission electron microscopy (TEM) as well as for chemical analysis by atomic absorption spectrometry. Cyclic voltammetry was used as a complementary technique to optical characterizations in the determination of semiconductor NCs band gap, obtaining approximate results. Novel nanocomposites of graphene derivatives (from citric acid and graphite) modified with NCs of MgCdTe were satisfactorily prepared by in situ hydrothermal synthesis and characterized by PL and TEM. Homemade modified carbon paste electrodes were built to evaluate the electrochemical behavior of the new composites, being used for the first time to the study of epinephrine and lidocaine eletrooxidation and their mixtures. The differential pulse voltammetry, proved to be a sensitive technique in both determination of electroactive species with detection limits that reached 9.2x10-8 mol.L-1, for epinephrine and 9.5x10-7 mol.L - 1 for lidocaine.